(3MGTjI GdOShbi Ydi Ce GdHQGgjfs - (3eMeO Hf CMeO Hf YQaI GdOShbis ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3bGd GdTjN GdYdGeI eMeO GdOThbi QMeg Gddg GdMeO dhGLH GdhLhO hHYO ajbhd GdYHO GdabjQ eMeO GdOShbi gPg JbjjOGJ Ydi TQM Ce GdHQGgje deDdagG eMeO GHf jhSa GdSfhSi LeYJgG ef JbQjQ TjNfG GdYdGeI CHj GdMSf Ydi Hf CMeO GdUYjOi GdYOhi hef ZjQs
(3BNQgG (B:s
(3hdjcf gPG NJGe gPg GdJbjjOGJ NJe Gddg dfG HGdMSfi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds